The design and optical properties of orthosilicate phosphor-bredigite-like structure as a green light component in WLED device - Ha Thanh Tung; Nguyen Le Thai; My Hanh Nguyen Thi; Huynh Thanh Thien (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2024)
We produce the green phosphor Ca14-xEuxMg2[SiO4]8 (CEMSO) to be a part of the white light emitting diodes (WLEDs), short for diodes that generate white illumination. It has wide emission spectra, reaching highest value as 505 nm when excited at the wavelength of 400 nm, which is caused by the 4f 65d–4f 7 shift (excited state to ground state) in an ion of Eu2+. The dipole-dipole interactivity appeared to be main energy shift method for the electric multipolar nature in CEMSO. We determine the critical distance to be 12.9 Å as well as 14.9 Å via a critical Eu2+ concentration and theory of Dexter regarding the energy shift. The CEMSO is integrated into the phosphor compound of yellow-phosphor/silicone for producing the UV-LED (395 nm). The impacts of CEMSO concentrations on UV-LED performances are determined. Significant improvements in chromatic uniformity and luminous output of the WLED are reported. The color rendering index (CRI) is not promoted, but this can be addressed by combining CEMSO green phosphor with red-luminescence materials, for example, red quantum dots or red phosphors.